GAMBARAN KEJADIAN KECACINGAN (SOIL TRANSMITTED HELMINTH), ASUPAN VITAMIN B12 DAN VITAMIN C PADA ANAK USIA SEKOLAH DASAR DI KOTA MAKASSAR - Hardiyanti Subair; Healthy Hidayanti; Abdul Salam (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2019)
Introduction: Worm infections will affect the intake, digestion, absorption, and metabolism of food.Worm infection can cause nutritional deficiencies in the form of calories, protein, and vitamins andblood loss which results in a decrease in endurance and cause disruption to child development.Objective: This study aims to describe the incidence of helminthiasis (soil transmitted helminth),intake of vitamin B12 and vitamin C in primary school-aged children in Makassar City. Materials andMethods: The type of research used is descriptive. Sampling was carried out using proportionalrandom sampling with a sample of 88 people in Makassar City representing the Manggala Districtarea namely SD Borong Jambu III Inpres and SD Inpres Perumnas Antang II / I and Tallo Districtnamely Rappokalling 67  Elementary School and Kaluku Bodoa Inpres Elementary School. Datacollection on children's characteristics was carried out by interviewing questionnaires and intakeusing a 2 × 24 hour food recall method, worm examination performed with the Kato Katz technique.Descriptive analysis was carried out using the SPSS application. Results: A total of 15.9% of childrenhad helminthiasis. Children who were positive for helminthiasis were more prevalent in male sexes,namely (22.9%) aged 10 years as much (17.6%) and living in coastal areas as much (23.3%). VitaminB12 intake showed more children who had more helminthiasis with adequate vitamin B12  intake whichwas as much as (85.7%). Whereas the status of helminthiasis based on vitamin C intake shows thatchildren who are positive have more worms with less vitamin C intake which is as much as (100%).Conclusions and Suggestions: Suggestions for the community, especially mothers and children, tomaintain home environmental sanitation, as well as the importance of consuming nutritious food